Level of Students Geometry Thinking on quadrilateral topic - Mayun Nggaba (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Quadrilateral is one of the geometry topics in the curriculum, and students at junior high school must understand the topic. Therefore, we researched 40 students (11/13 years) in Kambera District, East Sumba Regency, East Nusa Tenggara, to identify and describe students' geometric thinking levels. The research is descriptive qualitative research with data collection techniques and is a written test for the quadrilateral case. The data were analyzed using van Hiele's theory. The results showed that 1) only one-third of the students are at level 0 (visualization), i.e., students knew geometric pictures by observing the images or models. At this level, half of the students still need to improve in classifying the types of quadrilaterals, and 2) only a few students are at level 1. They can understand or know the properties of quadrilaterals. The written results found that almost all students needed help understanding the topic of quadrilaterals and their properties well. Nearly all students have yet to be able to recognize and classify the types of quadrilaterals well.